The changing triad of plague in Uganda: invasive black rats (Rattus rattus), indigenous small mammals, and their fleas. Issue 2 (18th November 2020) - Enscore, Russell E.; Babi, Nackson; Amatre, Gerald; Atiku, Linda; Eisen, Rebecca J.; Pepin, Kimberly M.; Vera‐Tudela, Rommelle; Sexton, Christopher; Gage, Kenneth L.
ABSTRACT: Rattus rattus was first reported from the West Nile Region of Uganda in 1961, an event that preceded the appearance of the first documented human plague outbreak in 1970. We investigated how invasive R. rattus and native small mammal populations, as well as their fleas, have changed in recent decades. Over an 18‐month period, a total of 2, 959 small mammals were captured, sampled, and examined for fleas, resulting in the identification of 20 small mammal taxa that were hosts to 5, 109 fleas (nine species). Over three‐fourths (75.8%) of captured mammals belonged to four taxa: R. rattus, which predominated inside huts, and Arvicanthis niloticus, Mastomys sp., and Crocidura sp., which were more common outside huts. These mammals were hosts for 85.8% of fleas collected, including the efficient plague vectors Xenopsylla cheopis and X. brasiliensis, as well as likely enzootic vectors, Dinopsyllus lypusus and Ctenophthalmus bacopus . Flea loads on small mammals were higher in certain environments in villages with a recent history of plague compared to those that lacked such a history. The significance of these results is discussed in relation to historical data, the initial spread of plague in the WNR and the continuing threat posed by the disease.